The Dimensions of Transformational Leadership and Its Organizational Effects in Public Universities in Saudi Arabia: A Systematic Review - Saad Alessa, Ghuzayyil (Frontiers in Psychology, 2021)
Organizations are dynamic entities that are constantly developing and changing. As such, these entities require leadership capable of managing transformations. Transformational leadership is an effective leadership model that focuses on adapting to existing environmental circumstances whether through internal information, human and monetary resources, or different external variables. This study aims to highlight the transformational leadership characteristics and their effects on Saudi public universities particularly, this study enlightens the most thirst need of testing the behavioral intention in public Universities of Saudi Arabia. To achieve this goal, many major databases were used. The period of the study was set from 2011 to 2020 as the topic of current transformational leadership within public universities in Saudi Arabia. There were totaled 47,400,000 studies on transformational leadership on google however, 22 studies were reviewed which were entirely conducted in Saudi Arabian Universities. The results demonstrated that in Saudi public universities, transformational leadership is practiced across four dimensions: ideal effect, inspirational motivation, intellectual stimulation, and individual consideration. The documentary research approach is used to review the most recent aspects of administrative literature on the theory of transformational leadership and its organizational outcomes. In addition, NVIVO 11 was used to make a thematic analysis of linkages between transformational leadership and organizational outcomes: organizational commitment, knowledge management practices, morale, employee empowerment, level of job satisfaction, administrative creativity, organizational citizenship behavior, and the level of transformation toward quality and job enrichment. Therefore, behavioral tendencies such as organizational commitment, empowerment, job satisfaction, and knowledge management practices have been studied more interestingly and critically. Furthermore, these behavioral aspects needed to be explored more in public Universities of Saudi Arabia.